Factors influencing equine embryo outcomes in OPU‑ICSI systems: Insights from a large‑scale program in Brazil - Vilceu Bordignon; Jose Buratini; Roger I. Cue; Victoria Barrilari; Marcos A. Gonçalves; Gustavo Merlini; Claudia B. Fernandes; Edward Squires; Jose H.F. Pontes; Perla D.C. Fleury (Journal of Equine Veterinary Science, 2026)

Promoting Research Excellence in Down Syndrome: Proceedings of the 5th International Conference of the Trisomy 21 Research Society - Fabio Di Domenico; Marzia Perluigi; Antonella Tramutola; Maria Giulia Bacalini; Daniella Balduino Victorino; Isabel Barroeta; Renata Bartesaghi; Angelo Carfi; Maria Carmona-Iragui; Ann D. Cohen; Alberto C. S. Costa; Floriana Costanzo; et al. (NeuroMolecular Medicine, 2026)
Down syndrome (DS), or trisomy 21 (T21), represents the most common genetic cause of intellectual disability worldwide and is associated with a wide range of medical, developmental, and neurodegenerative conditions, including a universal predisposition to early-onset Alzheimer’s disease (AD). Since its establishment in 2014, the Trisomy 21 Research Society (T21RS) has provided a global forum for advancing DS research across disciplines and promoting translational efforts to improve health and quality of life. Every two years, T21RS hosts an international scientific meeting that brings together researchers, clinicians, self-advocates, families, and industry stakeholders. In 2024, the 5th T21RS International Conference was held in Rome, Italy, from June 5 to 8, under the theme “Promoting Research Excellence in Down Syndrome.” The meeting brought together about 500 scientists from 26 countries across five continents, and more than 900 attendees overall, including families and caregivers. The scientific program featured 5 keynote lectures, 2 satellite meetings, 17 symposia, 7 nano symposia, 2 workshops, and 1 industry-focused session, totaling more than 150 oral presentations. More than 230 abstracts were presented as posters. The conference covered research across the lifespan of individuals with DS, spanning genomic and epigenetic regulation, molecular and cellular mechanisms, preclinical and experimental models, cognition and behavior, neurodevelopment, aging and neurodegeneration, co-occurring medical conditions, and therapeutic interventions. Dedicated sessions focused on capacity-building in DS research and societal engagement were established. Significantly, T21RS promoted inclusivity by supporting 60 young investigator fellowships, providing childcare awards, and organizing a two-day program for families and caregivers in collaboration with Italian DS associations. This proceeding summarizes the main scientific highlights of the 5th T21RS International Conference, reflecting the latest advances in DS biology, clinical research, biomarker development, and therapeutic innovation.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Renewed coexistence as a conceptual reframing of animal reintroductions to foster sustainable human–wildlife coexistence - Roger Edward Auster; Alan Puttock; Stewart Barr; Richard Brazier (Conservation Biology, 2026)
Wildlife reintroductions are socioecological processes entailing the intentional movement of organisms by people. In animal reintroductions, there is growing recognition of the importance of human dimensions and efforts to integrate these into reintroduction projects. To conceptually reframe reintroductions as processes of renewed coexistence (a coadaptive process through which sustainable human–wildlife interactions [HWIs] are fostered), we build upon existing understanding of HWIs and coexistence. Our conceptual framing acknowledges historical HWIs and recognizes that the reintroduced species may be new for people to coexist with today. This provides a long‐term, futures‐oriented perspective on reintroductions that goes beyond the return of an animal to fostering long‐term coexistence between humans and the reintroduced animal. This requires integration of social understandings and meaningful involvement of people from the outset and throughout feasibility, planning, and implementation. Further, we provide fresh insight on the subsequent transition phase by recognizing there to be a period where humans and reintroduced animals continue to coadapt as the situation transitions from a reintroduction project into a long‐term coexistence between humans and wild animals.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

High-throughput cell phenotype screening coupled with ion mobility spectrometry of American Aconitum - Yi Zhao; Dennis Y. Liu; Trevor N. Clark; Roger G. Linington; Edward J. Kennelly (Phytochemistry Letters, 2025)

Microscale analysis of the fish Knightia eocaena taphonomy: Implication of a preserved microbial community - Garrett A. Rogers; Dakota R. Pittinger; Edward L. Simpson; Kurt Friehauf (Palaeobiodiversity and Palaeoenvironments, 2025)
Microbial communities are important components controlling the fidelity of fossil fish preservation. The Eocene Green River Formation lagerstätten, exceptionally preserved fossil deposits, provides an opportunity to examine the role of microbial communities and their metabolic byproducts, such as chemical precipitated in this spectacularly preserved fish deposit, famous throughout the world. Field emission scanning electron microscope (FESEM) and energy dispersive spectroscopy system (EDS) examination of a well-preserved Knightia eocaena from the Eocene Green River Formation documents the presence of bacteriomorphs. Bacteriomorphs in a sample from the Fossil Butte Member of the Green River Formation consists of spherical structures, coccoid-type bacteria, fibres from two-sized populations of filamentous bacteria, probable filamentous cyanobacteria, capsule-shaped, and bacilliform bacteria, all associated with framboidal iron hydroxide. Bacteriomorphs consist of external molds composed of nanometer-scale calcium carbonate spheres. Fe-oxide framboids have an amorphous exterior and a sieve-like internal structure. The sieve-like structure consists of nanometer-scale pores, probable sites of bacterial cells with walls composed of 100-nanometer-scale spheres. Fe-oxides are consistent with bacterially mediated precipitation of pyrite followed by an oxidation event. Preserved bacteriomorphs are consistent with degradation of soft tissue, limiting the preservation of soft tissue and leaving bone and scales with no appreciable soft tissue. The microfossils are restricted to the skeleton and are not found in the surrounding rock matrix, suggesting larger microbial mats may not have been present and possibly did not have a significant impact on the preservation of this specimen.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Investigating stocking density, culture duration, and the combination ratio of artificial feed and fresh feed for mangrove crab Scylla serrata megalopae reared in pond-based net cages - Pedrita A. Caballero; Veronica R. Alava; Kyle Dymer L. Regatalio; Rheniel Dayrit; Joseph P. Faisan; Roger Edward P. Mamauag; Mercedes M. Pates; Gaudioso S. Pates (Aquaculture International, 2025)

Metabolite profiling and characterization of potential anticancer constituents from Garcinia subfalcata using UPLC-IMS-QTOF-MS - Fengke Lin; Michael J.J. Recchia; Trevor N. Clark; Edward J. Kennelly; Roger G. Linington; Chunlin Long (Food Chemistry, 2025)

Dietary Fiber Intake and Risk of Advanced and Aggressive Forms of Prostate Cancer: A Pooled Analysis of 15 Prospective Cohort Studies - Elkhansa Sidahmed; Stephen J. Freedland; Molin Wang; Kana Wu; Demetrius Albanes; Matt Barnett; Piet A. van den Brandt; Michael B. Cook; Graham G. Giles; Edward Giovannucci; Christopher A. Haiman; Susanna C. Larsson; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Evaluating SWOT's interferometric capabilities for mapping intertidal topography - Edward Salameh; Damien Desroches; Julien Deloffre; Roger Fjørtoft; Ernesto Tonatiuh Mendoza; Imen Turki; Laurent Froideval; Romain Levaillant; Simon Déchamps; Nicolas Picot; Benoit Laignel; Frédéric Frappart (Remote Sensing of Environment, 2024)

Recommendation for Clarifying FDA Policy in Evaluating “Sameness” of Higher Order Structure for Generic Peptide Therapeutics - Jessica A. Rogers-Crovak; Edward J. Delaney; David J. Detlefsen (The AAPS Journal, 2024)
Recognizing the approach of a dramatic expansion of peptide therapeutics reaching the marketplace in recent years, led by GLP-1 receptor agonists such as semaglutide and liraglutide, the Center for Drug Evaluation and Research (CDER) branch of the US Food and Drug Administration (FDA) issued a final guidance in 2021 that was intended to assist generic drug producers in meeting Abbreviated New Drug Application (ANDA) obligations to establish “sameness” of their active peptide drug relative to that produced by innovator companies. Research and a published report by FDA scientists on best practices followed, which promulgated the use of nuclear magnetic resonance (NMR) and principal component analysis (PCA) and established a quantitative standard by which “sameness” of higher order structure for the applicant’s peptide drug could be judged. A key requirement is that drug product samples be analyzed directly and non-invasively, a condition which in practice restricts sample modification to the addition of a small amount of deuterium oxide to allow signal lock and spectral data alignment (as required for NMR analysis). In the study described herein, data are presented to illustrate that 1) relatively small differences in sample pH can cause significant shifting of certain proton resonances, 2) that such resonance shifting is readily reversible and due to the degree of protonation of specific amino acid residues (rather than reflecting differences in higher order structure), and 3) that small differences in pH variability between sample cohorts can frequently cause failure to meet the quantitative benchmark established by the agency. Methodology is presented by which drug sample pHs can be aligned with minimal impact, and a recommendation is made that minor sample pH adjustments be allowed in assessing “sameness” of peptide drug higher order structure. Graphical Abstract

Optimizing the final rest period of sludge treatment wetlands: Assessment of biosolids quality - Ana Cano-Larrotta; Roger Castellnou; Edward Jair Pastor; Jessica Subirats; Víctor Matamoros; Enrica Uggetti (Journal of Environmental Management, 2024)

Remote sensing-based mangrove blue carbon assessment in the Asia-Pacific: A systematic review - Abhilash Dutta Roy; Pavithra S. Pitumpe Arachchige; Michael S. Watt; Apoorwa Kale; Mollie Davies; Joe Eu Heng; Redeat Daneil; G.A. Pabodha Galgamuwa; Lara G. Moussa; Kausila Timsina; Ewane Basil Ewane; Kerrylee Rogers; et al. (Science of The Total Environment, 2024)

Subglacial bedform and moat initiation beneath Rutford Ice Stream, West Antarctica - Rebecca Schlegel; Alex M. Brisbourne; Andrew M. Smith; Adam D. Booth; Tavi Murray; Edward C. King; Roger A. Clark (Geomorphology, 2024)

Blood flow rate to the femur of extinct kangaroos implies a higher locomotor intensity compared to living hopping macropods - Qiaohui Hu; Roger S. Seymour; Edward P. Snelling; Rod T. Wells (Journal of Mammalian Evolution, 2024)
The stocky skeletons and post-cranial anatomy of many extinct kangaroos indicate that they might have engaged in varied locomotor behaviors, rather than bipedal hopping, as their primary mode of locomotion. This study investigates support for this idea by estimating femoral bone perfusion, which is a correlate of locomotor intensity, in extinct kangaroos compared to living hopping species. Femur blood flow rates can be estimated from the sizes of nutrient foramina on the femur shaft of living and extinct species, without preservation of soft tissue. Estimated femur blood flow rates among the extinct Macropus , Protemnodon and Sthenurinae ( Sthenurus , Simosthenurus and Procoptodon ) are not significantly different from one another but are significantly greater than in living hopping macropods after accounting for the effect of body mass, consistent with their purportedly different locomotor style. The giant sthenurines have more robust femora than extrapolated from data of living hopping macropods, possibly due to the larger sthenurines requiring relatively stronger leg bones to support their heavier body weights, especially if loaded onto a single limb during bipedal striding.

Diverse pathways for climate resilience in marine fishery systems - Jacob G. Eurich; Whitney R. Friedman; Kristin M. Kleisner; Lily Z. Zhao; Christopher M. Free; Meghan Fletcher; Julia G. Mason; Kanae Tokunaga; Alba Aguion; Andrea Dell'Apa; Mark Dickey‐Collas; Rod Fujita; et al. (Fish and Fisheries, 2024)
Both the ecological and social dimensions of fisheries are being affected by climate change. As a result, policymakers, managers, scientists and fishing communities are seeking guidance on how to holistically build resilience to climate change. Numerous studies have highlighted key attributes of resilience in fisheries, yet concrete examples that explicitly link these attributes to social‐ecological outcomes are lacking. To better understand climate resilience, we assembled 18 case studies spanning ecological, socio‐economic, governance and geographic contexts. Using a novel framework for evaluating 38 resilience attributes, the case studies were systematically assessed to understand how attributes enable or inhibit resilience to a given climate stressor. We found population abundance, learning capacity, and responsive governance were the most important attributes for conferring resilience, with ecosystem connectivity, place attachment, and accountable governance scoring the strongest across the climate‐resilient fisheries. We used these responses to develop an attribute typology that describes robust sources of resilience, actionable priority attributes and attributes that are case specific or require research. We identified five fishery archetypes to guide stakeholders as they set long‐term goals and prioritize actions to improve resilience. Lastly, we found evidence for two pathways to resilience: (1) building ecological assets and strengthening communities, which we observed in rural and small‐scale fisheries, and (2) building economic assets and improving effective governance, which was demonstrated in urban and wealthy fisheries. Our synthesis presents a novel framework that can be directly applied to identify approaches, pathways and actionable levers for improving climate resilience in fishery systems.

Reproductive quality evaluation of male Indian white prawn Penaeus indicus broodstock fed diets supplemented with polychaete extracts ( Marphysa sp.) - Sheryll S. Santander-Avanceña; Rex Ferdinand M. Traifalgar; Erish G. Estante-Superio; Steve P. Janagap; Roger Edward P. Mamauag; Harold M. Monteclaro; Liberato V. Laureta; Gerald F. Quinitio (Invertebrate Reproduction & Development, 2023)

Inclusion of live mud polychaete (Marphysa iloiloensis) in the feeding regime improved the hatchery performance of domesticated Indian white shrimp (Penaeus indicus) - Erish G. Estante-Superio; Mary Anne E. Mandario; Sheryll S. Santander-Avanceña; Therese Marie M. Geanga; Fe Dolores Parado-Estepa; Roger Edward P. Mamauag (Regional Studies in Marine Science, 2023)

Histidine requirement of snubnose silver pompano Trachinotus blochii - Roger Edward Padua Mamauag; Janice Alano Ragaza (Animal Feed Science and Technology, 2023)

Mechanistic inference of the metabolic rates underlying $$^{13}$$C breath test curves - Andrew F. Brouwer; Gwenyth O. Lee; Robert J. Schillinger; Christine A. Edwards; Hannah Van Wyk; Roger Yazbeck; Douglas J. Morrison (Journal of Pharmacokinetics and Pharmacodynamics, 2023)

Updated guidelines for gene nomenclature in wheat - S. A. Boden; R. A. McIntosh; C. Uauy; S. G. Krattinger; J. Dubcovsky; W. J. Rogers; X. C. Xia; E. D. Badaeva; A. R. Bentley; G. Brown-Guedira; M. Caccamo; L. Cattivelli; et al. (Theoretical and Applied Genetics, 2023)
Key message Here, we provide an updated set of guidelines for naming genes in wheat that has been endorsed by the wheat research community. Abstract The last decade has seen a proliferation in genomic resources for wheat, including reference- and pan-genome assemblies with gene annotations, which provide new opportunities to detect, characterise, and describe genes that influence traits of interest. The expansion of genetic information has supported growth of the wheat research community and catalysed strong interest in the genes that control agronomically important traits, such as yield, pathogen resistance, grain quality, and abiotic stress tolerance. To accommodate these developments, we present an updated set of guidelines for gene nomenclature in wheat. These guidelines can be used to describe loci identified based on morphological or phenotypic features or to name genes based on sequence information, such as similarity to genes characterised in other species or the biochemical properties of the encoded protein. The updated guidelines provide a flexible system that is not overly prescriptive but provides structure and a common framework for naming genes in wheat, which may be extended to related cereal species. We propose these guidelines be used henceforth by the wheat research community to facilitate integration of data from independent studies and allow broader and more efficient use of text and data mining approaches, which will ultimately help further accelerate wheat research and breeding.

Extrapolating Contaminant Effects from Individuals to Populations: A Case Study on Nanoparticle Toxicity to Daphnia Fed Environmentally Relevant Food Levels - Louise M. Stevenson; Katherine E. Krattenmaker; Edward McCauley; Roger M. Nisbet (Archives of Environmental Contamination and Toxicology, 2022)

Genomic regions associated with resistance to soybean rust (Phakopsora pachyrhizi) under field conditions in soybean germplasm accessions from Japan, Indonesia and Vietnam - David R. Walker; Samuel C. McDonald; Donna K. Harris; H. Roger Boerma; James W. Buck; Edward J. Sikora; David B. Weaver; David L. Wright; James J. Marois; Zenglu Li (Theoretical and Applied Genetics, 2022)
Key message Eight soybean genomic regions, including six never before reported, were found to be associated with resistance to soybean rust ( Phakopsora pachyrhizi ) in the southeastern USA. Abstract Soybean rust caused by Phakopsora pachyrhizi is one of the most important foliar diseases of soybean [ Glycine max (L.) Merr.]. Although seven Rpp resistance gene loci have been reported, extensive pathotype variation in and among fungal populations increases the importance of identifying additional genes and loci associated with rust resistance. One hundred and ninety-one soybean plant introductions from Japan, Indonesia and Vietnam, and 65 plant introductions from other countries were screened for resistance to P. pachyrhizi under field conditions in the southeastern USA between 2008 and 2015. The results indicated that 84, 69, and 49% of the accessions from southern Japan, Vietnam or central Indonesia, respectively, had negative BLUP values, indicating less disease than the panel mean. A genome-wide association analysis using SoySNP50K Infinium BeadChip data identified eight genomic regions on seven chromosomes associated with SBR resistance, including previously unreported regions of Chromosomes 1, 4, 6, 9, 13, and 15, in addition to the locations of the Rpp3 and Rpp6 loci. The six unreported genomic regions might contain novel Rpp loci. The identification of additional sources of rust resistance and associated genomic regions will further efforts to develop soybean cultivars with broad and durable resistance to soybean rust in the southern USA.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The C-BIG Repository: an Institution-Level Open Science Platform - Samir Das; Rida Abou-Haidar; Henri Rabalais; Sonia Denise Lai Wing Sun; Zaliqa Rosli; Krishna Chatpar; Marie-Noëlle Boivin; Mahdieh Tabatabaei; Christine Rogers; Melanie Legault; Derek Lo; Clotilde Degroot; et al. (Neuroinformatics, 2022)
In January 2016, the Montreal Neurological Institute-Hospital (The Neuro) declared itself an Open Science organization. This vision extends beyond efforts by individual scientists seeking to release individual datasets, software tools, or building platforms that provide for the free dissemination of such information. It involves multiple stakeholders and an infrastructure that considers governance, ethics, computational resourcing, physical design, workflows, training, education, and intra-institutional reporting structures. The C-BIG repository was built in response as The Neuro’s institutional biospecimen and clinical data repository, and collects biospecimens as well as clinical, imaging, and genetic data from patients with neurological disease and healthy controls. It is aimed at helping scientific investigators, in both academia and industry, advance our understanding of neurological diseases and accelerate the development of treatments. As many neurological diseases are quite rare, they present several challenges to researchers due to their small patient populations. Overcoming these challenges required the aggregation of datasets from various projects and locations. The C-BIG repository achieves this goal and stands as a scalable working model for institutions to collect, track, curate, archive, and disseminate multimodal data from patients. In November 2020, a Registered Access layer was made available to the wider research community at https://cbigr-open.loris.ca , and in May 2021 fully open data will be released to complement the Registered Access data. This article outlines many of the aspects of The Neuro’s transition to Open Science by describing the data to be released, C-BIG’s full capabilities, and the design aspects that were implemented for effective data sharing.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Contrasting climate velocity impacts in warm and cool locations show that effects of marine warming are worse in already warmer temperate waters - Philina A. English; Eric J. Ward; Christopher N. Rooper; Robyn E. Forrest; Luke A. Rogers; Karen L. Hunter; Andrew M. Edwards; Brendan M. Connors; Sean C. Anderson (Fish and Fisheries, 2022)
Species responses to climate change are often measured at broad spatiotemporal scales, which can miss the fine‐scale changes that are most relevant to conservation and fisheries management. We develop a scaleable geostatistical approach to assess how juvenile and adult fish distributions have been shaped by changes in bottom temperature and dissolved oxygen over a recent decade of warming in the northeast Pacific. Across 38 demersal fishes, biomass trends were associated negatively with warming and positively with dissolved oxygen, but when trends in both biomass and climate were converted to velocities—the speed and direction a population would have to move to maintain consistent conditions—the effect of temperature change differed depending on local conditions. In the warmest locations, warming velocities were associated with negative biotic velocities for 19 of 69 species‐maturity combinations, and yet were almost always associated with stable or positive biotic velocities in the coolest locations (64 of 69). These spatially consistent biomass declines (negative biotic velocities) in the warmest locations and increases in cooler locations suggest a redistribution of species with the potential for new ecological and fisheries interactions. After controlling for temperature, the more spatially consistent effects of dissolved oxygen were often negative, suggesting a mechanism other than hypoxia avoidance—potentially changes in primary production. Our approach identifies the species and locations that are most sensitive to observed changes in the environment at any scale, thus facilitating future vulnerability assessments.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Statistical upscaling of ecosystem CO 2 fluxes across the terrestrial tundra and boreal domain: Regional patterns and uncertainties - Anna‐Maria Virkkala; Juha Aalto; Brendan M. Rogers; Torbern Tagesson; Claire C. Treat; Susan M. Natali; Jennifer D. Watts; Stefano Potter; Aleksi Lehtonen; Marguerite Mauritz; Edward A. G. Schuur; John Kochendorfer; et al. (Global Change Biology, 2021)
The regional variability in tundra and boreal carbon dioxide (CO 2 ) fluxes can be high, complicating efforts to quantify sink‐source patterns across the entire region. Statistical models are increasingly used to predict (i.e., upscale) CO 2 fluxes across large spatial domains, but the reliability of different modeling techniques, each with different specifications and assumptions, has not been assessed in detail. Here, we compile eddy covariance and chamber measurements of annual and growing season CO 2 fluxes of gross primary productivity (GPP), ecosystem respiration (ER), and net ecosystem exchange (NEE) during 1990–2015 from 148 terrestrial high‐latitude (i.e., tundra and boreal) sites to analyze the spatial patterns and drivers of CO 2 fluxes and test the accuracy and uncertainty of different statistical models. CO 2 fluxes were upscaled at relatively high spatial resolution (1 km 2 ) across the high‐latitude region using five commonly used statistical models and their ensemble, that is, the median of all five models, using climatic, vegetation, and soil predictors. We found the performance of machine learning and ensemble predictions to outperform traditional regression methods. We also found the predictive performance of NEE‐focused models to be low, relative to models predicting GPP and ER. Our data compilation and ensemble predictions showed that CO 2 sink strength was larger in the boreal biome (observed and predicted average annual NEE −46 and −29 g C m −2 yr −1 , respectively) compared to tundra (average annual NEE +10 and −2 g C m −2 yr −1 ). This pattern was associated with large spatial variability, reflecting local heterogeneity in soil organic carbon stocks, climate, and vegetation productivity. The terrestrial ecosystem CO 2 budget, estimated using the annual NEE ensemble prediction, suggests the high‐latitude region was on average an annual CO 2 sink during 1990–2015, although uncertainty remains high.

Ontogenetic scaling of the gastrointestinal tract of a marsupial foregut fermenter, the western grey kangaroo Macropus fuliginosus melanops - Adam J. Munn; Edward P. Snelling; David A. Taggart; Roger S. Seymour (Journal of Comparative Physiology B, 2021)

Relationships among white-tailed deer density, harvest, and landscape metrics in TN, USA - Heidi L. Adams; Robert E. Kissell; Daryl Ratajczak; Edward L. Warr; Roger D. Applegate; Lynn Barrett; Tabitha Lavacot; David Graves (European Journal of Wildlife Research, 2020)
Landscape and harvest indices are frequently used to represent white-tailed deer ( Odocoileus virginianus ) density. However, the relationship between deer density and specific landscape indices is unclear. Harvest is another metric often used to estimate deer density. Our objective was to model the relationship among deer density, landscape metrics, and harvest density of deer in TN, USA. We estimated deer density across 11 regions in 2011 using distance sampling techniques. We developed 18 a priori models to assess relationships among deer density, harvest density, and landscape metrics. Estimates of deer density ranged from 1.85 to 19.99 deer/km 2 . Deer density was best predicted by harvest density and harvest density + percent woody area. However, harvest density was the only important variable in predicting deer density (Σω i = 0.700). Results of this study emphasize the significance of harvest density in deer management. While the importance of harvest as a management tool for deer is likely to increase as landscapes are fragmented and urbanized, specific management guidelines should be based upon deer densities and landscape metrics when they are important.

A Review on the Factors Affecting the Deposition, Retention, and Biodegradation of Oil Stranded on Beaches and Guidelines for Designing Laboratory Experiments - Michel Boufadel; Xiaolong Geng; Chunjiang An; Edward Owens; Zhi Chen; Kenneth Lee; Elliott Taylor; Roger C. Prince (Current Pollution Reports, 2019)

Decision support platforms for climate change adaptation: an overview and introduction - Jean P. Palutikof; Roger B. Street; Edward P. Gardiner (Climatic Change, 2019)

Looking to the future: guidelines for decision support as adaptation practice matures - Jean P. Palutikof; Roger B. Street; Edward P. Gardiner (Climatic Change, 2019)

Antibiotic misuse in respiratory tract infections in children and adults—a prospective, multicentre study (TAILORED Treatment) - Chantal B. van Houten; Asi Cohen; Dan Engelhard; John P. Hays; Roger Karlsson; Edward Moore; David Fernández; Racheli Kreisberg; Laurence V. Collins; Wouter de Waal; Karin M. de Winter-de Groot; Tom F. W. Wolfs; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Current status of the Botryosphaeriaceae in Australia - Treena I. Burgess; Yu Pei Tan; Jeff Garnas; Jacqueline Edwards; Kelly A. Scarlett; Lucas A. Shuttleworth; Rosalie Daniel; Elizabeth K. Dann; Louisamarie E. Parkinson; Quang Dinh; Roger G. Shivas; Fahimeh Jami (Australasian Plant Pathology, 2019)

Australian cultures of Botryosphaeriaceae held in Queensland and Victoria plant pathology herbaria revisited - Yu Pei Tan; Roger G. Shivas; Thomas S. Marney; Jacqueline Edwards; John Dearnaley; Fahimeh Jami; Treena I. Burgess (Australasian Plant Pathology, 2019)

Impact of Glutathione Peroxidase-1 (Gpx1) Genotype on Selenoenzyme and Transcript Expression When Repleting Selenium-Deficient Mice - Roger A. Sunde; Edward T. Zemaitis; Andrew B. Blink; Julia A. Lawinger (Biological Trace Element Research, 2018)

Ameliorating the adverse cardiorespiratory effects of chemical immobilization by inducing general anaesthesia in sheep and goats: implications for physiological studies of large wild mammals - Adian Izwan; Edward P. Snelling; Roger S. Seymour; Leith C. R. Meyer; Andrea Fuller; Anna Haw; Duncan Mitchell; Anthony P. Farrell; Mary-Ann Costello; Shane K. Maloney (Journal of Comparative Physiology B, 2018)

Cross‐scale controls on carbon emissions from boreal forest megafires - Xanthe J. Walker; Brendan M. Rogers; Jennifer L. Baltzer; Steven G. Cumming; Nicola J. Day; Scott J. Goetz; Jill F. Johnstone; Edward A. G. Schuur; Merritt R. Turetsky; Michelle C. Mack (Global Change Biology, 2018)
Climate warming and drying is associated with increased wildfire disturbance and the emergence of megafires in North American boreal forests. Changes to the fire regime are expected to strongly increase combustion emissions of carbon (C) which could alter regional C balance and positively feedback to climate warming. In order to accurately estimate C emissions and thereby better predict future climate feedbacks, there is a need to understand the major sources of heterogeneity that impact C emissions at different scales. Here, we examined 211 field plots in boreal forests dominated by black spruce ( Picea mariana ) or jack pine ( Pinus banksiana ) of the Northwest Territories ( NWT ), Canada after an unprecedentedly large area burned in 2014. We assessed both aboveground and soil organic layer ( SOL ) combustion, with the goal of determining the major drivers in total C emissions, as well as to develop a high spatial resolution model to scale emissions in a relatively understudied region of the boreal forest. On average, 3.35 kg C m −2 was combusted and almost 90% of this was from SOL combustion. Our results indicate that black spruce stands located at landscape positions with intermediate drainage contribute the most to C emissions. Indices associated with fire weather and date of burn did not impact emissions, which we attribute to the extreme fire weather over a short period of time. Using these results, we estimated a total of 94.3 Tg C emitted from 2.85 Mha of burned area across the entire 2014 NWT fire complex, which offsets almost 50% of mean annual net ecosystem production in terrestrial ecosystems of Canada. Our study also highlights the need for fine‐scale estimates of burned area that represent small water bodies and regionally specific calibrations of combustion that account for spatial heterogeneity in order to accurately model emissions at the continental scale.

Detecting early warning signals of tree mortality in boreal North America using multiscale satellite data - Brendan M. Rogers; Kylen Solvik; Edward H. Hogg; Junchang Ju; Jeffrey G. Masek; Michael Michaelian; Logan T. Berner; Scott J. Goetz (Global Change Biology, 2018)
Increasing tree mortality from global change drivers such as drought and biotic infestations is a widespread phenomenon, including in the boreal zone where climate changes and feedbacks to the Earth system are relatively large. Despite the importance for science and management communities, our ability to forecast tree mortality at landscape to continental scales is limited. However, two independent information streams have the potential to inform and improve mortality forecasts: repeat forest inventories and satellite remote sensing. Time series of tree‐level growth patterns indicate that productivity declines and related temporal dynamics often precede mortality years to decades before death. Plot‐level productivity, in turn, has been related to satellite‐based indices such as the Normalized difference vegetation index ( NDVI ). Here we link these two data sources to show that early warning signals of mortality are evident in several NDVI ‐based metrics up to 24 years before death. We focus on two repeat forest inventories and three NDVI products across western boreal North America where productivity and mortality dynamics are influenced by periodic drought. These data sources capture a range of forest conditions and spatial resolution to highlight the sensitivity and limitations of our approach. Overall, results indicate potential to use satellite NDVI for early warning signals of mortality. Relationships are broadly consistent across inventories, species, and spatial resolutions, although the utility of coarse‐scale imagery in the heterogeneous aspen parkland was limited. Longer‐term NDVI data and annually remeasured sites with high mortality levels generate the strongest signals, although we still found robust relationships at sites remeasured at a typical 5 year frequency. The approach and relationships developed here can be used as a basis for improving forest mortality models and monitoring systems.

Development of a rapid MALDI-TOF MS based epidemiological screening method using MRSA as a model organism - Åsa Lindgren; Nahid Karami; Roger Karlsson; Christina Åhrén; Martin Welker; Edward R. B. Moore; Liselott Svensson Stadler (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

SDF-1 induces TNF-mediated apoptosis in cardiac myocytes - Andrew A. Jarrah; Martina Schwarskopf; Edward R. Wang; Thomas LaRocca; Ashwini Dhume; Shihong Zhang; Lahouria Hadri; Roger J. Hajjar; Alison D. Schecter; Sima T. Tarzami (Apoptosis, 2018)

Colletotrichum species in Australia - Roger G. Shivas; Yu Pei Tan; Jacqueline Edwards; Quang Dinh; Aaron Maxwell; Vera Andjic; José R. Liberato; Chris Anderson; Dean R. Beasley; Kaylene Bransgrove; Lindy M. Coates; Karren Cowan; et al. (Australasian Plant Pathology, 2016)

Mapping adipose and muscle tissue expression quantitative trait loci in African Americans to identify genes for type 2 diabetes and obesity - Satria P. Sajuthi; Neeraj K. Sharma; Jeff W. Chou; Nicholette D. Palmer; David R. McWilliams; John Beal; Mary E. Comeau; Lijun Ma; Jorge Calles-Escandon; Jamehl Demons; Samantha Rogers; Kristina Cherry; et al. (Human Genetics, 2016)

Daphnia magna’s sense of competition: intra-specific interactions (ISI) alter life history strategies and increase metals toxicity - Kurt A. Gust; Alan J. Kennedy; Nicolas L. Melby; Mitchell S. Wilbanks; Jennifer Laird; Barbara Meeks; Erik B. Muller; Roger M. Nisbet; Edward J. Perkins (Ecotoxicology, 2016)

Alcohol exposure in utero is associated with decreased gray matter volume in neonates - Kirsten A. Donald; J. P. Fouche; Annerine Roos; Nastassja Koen; Fleur M. Howells; Edward P. Riley; Roger P. Woods; Heather J. Zar; Katherine L. Narr; Dan J. Stein (Metabolic Brain Disease, 2016)

Human activities and climate variability drive fast‐paced change across the world's estuarine–coastal ecosystems - James E. Cloern; Paulo C. Abreu; Jacob Carstensen; Laurent Chauvaud; Ragnar Elmgren; Jacques Grall; Holly Greening; John Olov Roger Johansson; Mati Kahru; Edward T. Sherwood; Jie Xu; Kedong Yin (Global Change Biology, 2016)
Time series of environmental measurements are essential for detecting, measuring and understanding changes in the Earth system and its biological communities. Observational series have accumulated over the past 2–5 decades from measurements across the world's estuaries, bays, lagoons, inland seas and shelf waters influenced by runoff. We synthesize information contained in these time series to develop a global view of changes occurring in marine systems influenced by connectivity to land. Our review is organized around four themes: (i) human activities as drivers of change; (ii) variability of the climate system as a driver of change; (iii) successes, disappointments and challenges of managing change at the sea‐land interface; and (iv) discoveries made from observations over time. Multidecadal time series reveal that many of the world's estuarine–coastal ecosystems are in a continuing state of change, and the pace of change is faster than we could have imagined a decade ago. Some have been transformed into novel ecosystems with habitats, biogeochemistry and biological communities outside the natural range of variability. Change takes many forms including linear and nonlinear trends, abrupt state changes and oscillations. The challenge of managing change is daunting in the coastal zone where diverse human pressures are concentrated and intersect with different responses to climate variability over land and over ocean basins. The pace of change in estuarine–coastal ecosystems will likely accelerate as the human population and economies continue to grow and as global climate change accelerates. Wise stewardship of the resources upon which we depend is critically dependent upon a continuing flow of information from observations to measure, understand and anticipate future changes along the world's coastlines.

Toward the genetic origins of a potentially non-native population of threespine stickleback (Gasterosteus aculeatus) in Alberta - Andrew M. Rezansoff; Erika Crispo; Christopher Blair; Edward Cruz; Jun Kitano; Steven M. Vamosi; Sean M. Rogers (Conservation Genetics, 2015)

Use of structured expert judgment to forecast invasions by bighead and silver carp in Lake Erie - Marion E. Wittmann; Roger M. Cooke; John D. Rothlisberger; Edward S. Rutherford; Hongyan Zhang; Doran M. Mason; David M. Lodge (Conservation Biology, 2015)
Identifying which nonindigenous species will become invasive and forecasting the damage they will cause is difficult and presents a significant problem for natural resource management. Often, the data or resources necessary for ecological risk assessment are incomplete or absent, leaving environmental decision makers ill equipped to effectively manage valuable natural resources. Structured expert judgment (SEJ) is a mathematical and performance‐based method of eliciting, weighting, and aggregating expert judgments. In contrast to other methods of eliciting and aggregating expert judgments (where, for example, equal weights may be assigned to experts), SEJ weights each expert on the basis of his or her statistical accuracy and informativeness through performance measurement on a set of calibration variables. We used SEJ to forecast impacts of nonindigenous Asian carp ( Hypophthalmichthys spp.) in Lake Erie, where it is believed not to be established. Experts quantified Asian carp biomass, production, and consumption and their impact on 4 fish species if Asian carp were to become established. According to experts, in Lake Erie Asian carp have the potential to achieve biomass levels that are similar to the sum of biomasses for several fishes that are harvested commercially or recreationally. However, the impact of Asian carp on the biomass of these fishes was estimated by experts to be small, relative to long term average biomasses, with little uncertainty. Impacts of Asian carp in tributaries and on recreational activities, water quality, or other species were not addressed. SEJ can be used to quantify key uncertainties of invasion biology and also provide a decision‐support tool when the necessary information for natural resource management and policy is not available. El Uso de Juicio Experto Estructurado para Predecir Invasiones de Carpas Asiáticas en el Lago Erie

Operationalizing resilience for adaptive coral reef management under global environmental change - Kenneth R.N. Anthony; Paul A. Marshall; Ameer Abdulla; Roger Beeden; Chris Bergh; Ryan Black; C. Mark Eakin; Edward T. Game; Margaret Gooch; Nicholas A.J. Graham; Alison Green; Scott F. Heron; et al. (Global Change Biology, 2015)
Cumulative pressures from global climate and ocean change combined with multiple regional and local‐scale stressors pose fundamental challenges to coral reef managers worldwide. Understanding how cumulative stressors affect coral reef vulnerability is critical for successful reef conservation now and in the future. In this review, we present the case that strategically managing for increased ecological resilience (capacity for stress resistance and recovery) can reduce coral reef vulnerability (risk of net decline) up to a point. Specifically, we propose an operational framework for identifying effective management levers to enhance resilience and support management decisions that reduce reef vulnerability. Building on a system understanding of biological and ecological processes that drive resilience of coral reefs in different environmental and socio‐economic settings, we present an Adaptive Resilience‐Based management ( ARBM ) framework and suggest a set of guidelines for how and where resilience can be enhanced via management interventions. We argue that press‐type stressors (pollution, sedimentation, overfishing, ocean warming and acidification) are key threats to coral reef resilience by affecting processes underpinning resistance and recovery, while pulse‐type (acute) stressors (e.g. storms, bleaching events, crown‐of‐thorns starfish outbreaks) increase the demand for resilience. We apply the framework to a set of example problems for Caribbean and Indo‐Pacific reefs. A combined strategy of active risk reduction and resilience support is needed, informed by key management objectives, knowledge of reef ecosystem processes and consideration of environmental and social drivers. As climate change and ocean acidification erode the resilience and increase the vulnerability of coral reefs globally, successful adaptive management of coral reefs will become increasingly difficult. Given limited resources, on‐the‐ground solutions are likely to focus increasingly on actions that support resilience at finer spatial scales, and that are tightly linked to ecosystem goods and services.

The Virtual Toxicology Service: Wearable Head-Mounted Devices for Medical Toxicology - Peter R. Chai; Roger Y. Wu; Megan L. Ranney; Paul S. Porter; Kavita M. Babu; Edward W. Boyer (Journal of Medical Toxicology, 2014)

Interactions of time of day and sleep with between-session habituation and extinction memory in young adult males - Edward F. Pace-Schott; Lauren E. Tracy; Zoe Rubin; Adrian G. Mollica; Jeffrey M. Ellenbogen; Matt T. Bianchi; Mohammed R. Milad; Roger K. Pitman; Scott P. Orr (Experimental Brain Research, 2014)

Plant litter effects on soil nutrient availability and vegetation dynamics: changes that occur when annual grasses invade shrub-steppe communities - Sheel Bansal; Roger L. Sheley; Bob Blank; Edward A. Vasquez (Plant Ecology, 2014)

Improving the science-policy dialogue to meet the challenges of biodiversity conservation: having conversations rather than talking at one-another - Juliette C. Young; Kerry A. Waylen; Simo Sarkki; Steve Albon; Ian Bainbridge; Estelle Balian; James Davidson; David Edwards; Roddy Fairley; Ceri Margerison; Davy McCracken; Roger Owen; et al. (Biodiversity and Conservation, 2014)

Longitudinal decline of lower extremity muscle power in healthy and mobility-limited older adults: influence of muscle mass, strength, composition, neuromuscular activation and single fiber contractile properties - Kieran F. Reid; Evan Pasha; Gheorghe Doros; David J. Clark; Carolynn Patten; Edward M. Phillips; Walter R. Frontera; Roger A. Fielding (European Journal of Applied Physiology, 2014)

Reliable, verifiable and efficient monitoring of biodiversity via metabarcoding - Yinqiu Ji; Louise Ashton; Scott M. Pedley; David P. Edwards; Yong Tang; Akihiro Nakamura; Roger Kitching; Paul M. Dolman; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; Wayne W. Hsu; et al. (Ecology Letters, 2013)
To manage and conserve biodiversity, one must know what is being lost, where, and why, as well as which remedies are likely to be most effective. Metabarcoding technology can characterise the species compositions of mass samples of eukaryotes or of environmental DNA . Here, we validate metabarcoding by testing it against three high‐quality standard data sets that were collected in Malaysia (tropical), China (subtropical) and the United Kingdom (temperate) and that comprised 55,813 arthropod and bird specimens identified to species level with the expenditure of 2,505 person‐hours of taxonomic expertise. The metabarcode and standard data sets exhibit statistically correlated alpha‐ and beta‐diversities, and the two data sets produce similar policy conclusions for two conservation applications: restoration ecology and systematic conservation planning. Compared with standard biodiversity data sets, metabarcoded samples are taxonomically more comprehensive, many times quicker to produce, less reliant on taxonomic expertise and auditable by third parties, which is essential for dispute resolution.

The Site-Wise Log-Likelihood Score is a Good Predictor of Genes under Positive Selection - Huai-Chun Wang; Edward Susko; Andrew J. Roger (Journal of Molecular Evolution, 2013)

Identification of serum analytes and metabolites associated with aerobic capacity - Michael S. Lustgarten; Lori Lyn Price; Tanya Logvinenko; Christos Hatzis; Nandan Padukone; Nicholas V. Reo; Edward M. Phillips; Dylan Kirn; John Mills; Roger A. Fielding (European Journal of Applied Physiology, 2013)

Soil warming increases plant species richness but decreases germination from the alpine soil seed bank - Gemma L. Hoyle; Susanna E. Venn; Kathryn J. Steadman; Roger B. Good; Edward J. McAuliffe; Emlyn R. Williams; Adrienne B. Nicotra (Global Change Biology, 2013)
Global warming is occurring more rapidly above the treeline than at lower elevations and alpine areas are predicted to experience above average warming in the future. Temperature is a primary factor in stimulating seed germination and regulating changes in seed dormancy status. Thus, plant regeneration from seed will be crucial to the persistence, migration and post disturbance recruitment of alpine plants in future climates. Here, we present the first assessment of the impact of soil warming on germination from the persistent alpine soil seed bank. Contrary to expectations, soil warming lead to reduced overall germination from the soil seed bank. However, germination response to soil temperature was species specific such that total species richness actually increased by nine with soil warming. We further explored the system by assessing the prevalence of seed dormancy and germination response to soil disturbance, the frequency of which is predicted to increase under climate change. Seeds of a significant proportion of species demonstrated physiological dormancy mechanisms and germination of several species appeared to be intrinsically linked to soil disturbance. In addition, we found no evidence of subalpine species and little evidence of exotic weed species in the soil, suggesting that the soil seed bank will not facilitate their invasion of the alpine zone. In conclusion, changes in recruitment via the alpine soil seed bank can be expected under climate change, as a result of altered dormancy alleviation and germination cues. Furthermore, the alpine soil seed bank, and the species richness therein, has the potential to help maintain local species diversity, support species range shift and moderate species dominance. Implications for alpine management and areas for further study are also discussed.

Conformational changes at the nucleotide site in the presence of bound ADP do not set the velocity of fast Drosophila myosins - Catherine C. Eldred; Nariman Naber; Edward Pate; Roger Cooke; Douglas M. Swank (Journal of Muscle Research and Cell Motility, 2013)

Muscle power failure in mobility-limited older adults: preserved single fiber function despite lower whole muscle size, quality and rate of neuromuscular activation - Kieran F. Reid; Gheorghe Doros; David J. Clark; Carolynn Patten; Robert J. Carabello; Gregory J. Cloutier; Edward M. Phillips; Lisa S. Krivickas; Walter R. Frontera; Roger A. Fielding (European Journal of Applied Physiology, 2012)

(2-Methoxyethoxy)acetic acid: a urinary biomarker of exposure for jet fuel JP-8 - Clayton B’Hymer; Patricia Mathias; Edward Krieg; Kenneth L. Cheever; Christine A. Toennis; John C. Clark; James S. Kesner; Roger L. Gibson; Mary Ann Butler (International Archives of Occupational and Environmental Health, 2012)

Removing human immunodeficiency virus (HIV) from human blood using immobilized heparin - Roger A. Nassar; Edward P. Browne; Jianzhu Chen; Alexander M. Klibanov (Biotechnology Letters, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Advances in winter pulse pathology research in Australia - Moin U. Salam; Jennifer A. Davidson; Geoff J. Thomas; Rebecca Ford; Roger A. C. Jones; Kurt D. Lindbeck; William J. MacLeod; Rohan B. E. Kimber; Jean Galloway; Nitin Mantri; Joop A. G. van Leur; Brenda A. Coutts; et al. (Australasian Plant Pathology, 2011)

Growth, nutrient utilization, oxidative condition, and element composition of juvenile red sea bream Pagrus major fed with fermented soybean meal and scallop by-product blend as fishmeal replacement - Md. Abdul Kader; Shunsuke Koshio; Manabu Ishikawa; Saichiro Yokoyama; Mahbuba Bulbul; Yuki Honda; Roger Edward Mamauag; Asda Laining (Fisheries Science, 2011)

Fractured bedrock and saprolite hydrogeologic controls on groundwater/surface-water interaction: a conceptual model (Australia) - Edward W. Banks; Craig T. Simmons; Andrew J. Love; Roger Cranswick; Adrian D. Werner; Erick A. Bestland; Martin Wood; Tania Wilson (Hydrogeology Journal, 2009)

APPLICATIONS IN COASTAL MODELING AND FORECASTING - Pierre De Mey; Peter Craig; Fraser Davidson; Christopher Edwards; Yoichi Ishikawa; John Kindle; Roger Proctor; Keith Thompson; Jiang Zhu (Oceanography, 2009)

Mhc haplotype H6 is associated with sustained control of SIVmac251 infection in Mauritian cynomolgus macaques - Edward T. Mee; Neil Berry; Claire Ham; Ulrike Sauermann; Maria T. Maggiorella; Frédéric Martinon; Ernst J. Verschoor; Jonathan L. Heeney; Roger Le Grand; Fausto Titti; Neil Almond; Nicola J. Rose (Immunogenetics, 2009)

Characterization of twenty-one microsatellites developed from Propithecus diadema - Roger Ramarokoto; Runhua Lei; Justin Vincent; Sabine Day; Gary D. Shore; Rick A. Brenneman; Edward E. Louis (Conservation Genetics, 2008)

Carbon allocation in boreal black spruce forests across regions varying in soil temperature and precipitation - JASON G. VOGEL; BEN P. BOND‐LAMBERTY; EDWARD A. G. SCHUUR; STITH T. GOWER; MICHELLE C. MACK; KARI E. B. O'CONNELL; DAVID W. VALENTINE; ROGER W. RUESS (Global Change Biology, 2008)
A common hypothesis for northern ecosystems is that low soil temperatures inhibit plant productivity. To address this hypothesis, we reviewed how separate components of ecosystem carbon (C) cycling varied along a soil temperature gradient for nine well‐drained, relatively productive boreal black spruce ( Picea mariana Mill. [B.S.P.]) forests in Alaska, USA, and Saskatchewan and Manitoba, Canada. Annual soil temperature [expressed as soil summed degree days (SDD)] was positively correlated with aboveground net primary productivity (ANPP), while negatively correlated with total belowground carbon flux (TBCF). The partitioning of C to ANPP at the expense of root processes represented a nearly 1 : 1 tradeoff across the soil temperature gradient, which implied that the amount of C cycling through these black spruce ecosystems was relatively insensitive to variation in SDD. Moreover, the rate at which C accumulated in the ecosystem since the last stand replacing fire was unrelated to SDD, but SDD was positively correlated to the ratio of spruce‐biomass : forest‐floor‐mass. Thus, plant partitioning of C and the distribution of ecosystem C were apparently affected by soil temperature, although across regions, precipitation co‐varied with soil temperature. These two factors likely correlated with one another because of precipitation's influence on soil heat balance, suggesting that a soil temperature–precipitation interaction could be responsible for the shifts in C allocation. Nonetheless, our results highlight that for this boreal ecosystem, ANPP and TBCF can be negatively correlated. In tropical and temperate forests, TBCF and ANPP have been reported as positively correlated, and our results may reflect the unique interactions between soil temperature, forest floor accumulation, rooting depth, and nutrient availability that characterize the black spruce forest type.

Topological Estimation Biases with Covarion Evolution - Huai-Chun Wang; Edward Susko; Matthew Spencer; Andrew J. Roger (Journal of Molecular Evolution, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Stage-structured cycles generate strong fitness-equalizing mechanisms - William A. Nelson; Edward McCauley; Roger M. Nisbet (Evolutionary Ecology, 2007)

Effects of acute fatigue on the volitional and magnetically-evoked electromechanical delay of the knee flexors in males and females - Claire Minshull; Nigel Gleeson; Michelle Walters-Edwards; Roger Eston; David Rees (European Journal of Applied Physiology, 2007)

Evidence for adiabatic decompression melting in the Southern Mariana Arc from high-Mg lavas and melt inclusions - Edward J. Kohut; Robert J. Stern; Adam J. R. Kent; Roger L. Nielsen; Sherman H. Bloomer; Matthew Leybourne (Contributions to Mineralogy and Petrology, 2006)

Biases in Phylogenetic Estimation Can Be Caused by Random Sequence Segments - Edward Susko; Mathew Spencer; Andrew J. Roger (Journal of Molecular Evolution, 2005)

Structures of Mesocirculations Producing Tornadoes Associated with Tropical Cyclone Frances (1998) - Gandikota V. Rao; Joshua W. Scheck; Roger Edwards; Joseph T. Schaefer (Pure and Applied Geophysics, 2005)

Exogenous IL-7 induces Fas-mediated human neuronal apoptosis: potential effects during human immunodeficiency virus type 1 infection - Giuseppe Nunnari; Yan Xu; Edward A Acheampong; Jianhua Fang; Rene Daniel; Chune Zhang; Hui Zhang; Muhammad Mukhtar; Roger J. Pomerantz (Journal of NeuroVirology, 2005)

A gene-driven ENU-based approach to generating an allelic series in any gene - Mohamed Mohideen Quwailid; Alison Hugill; Neil Dear; Lucie Vizor; Sara Wells; Emma Horner; Shelly Fuller; Jessica Weedon; Hamish McMath; Paul Woodman; David Edwards; David Campbell; et al. (Mammalian Genome, 2004)

Melt inclusion formation mechanisms and compositional effects in high-An feldspar and high-Fo olivine in anhydrous mafic silicate liquids - Edward Kohut; Roger L. Nielsen (Contributions to Mineralogy and Petrology, 2004)

Three-Dimensional Scalar Microfront Systems in a Large-Eddy Simulation of Vegetation Canopy Flow - Li Fitzmaurice; Roger H. Shaw; Kyaw Tha Paw U; Edward G. Patton (Boundary-Layer Meteorology, 2004)

Extracellular freezing in leaves of freezing-sensitive species - Edward Ashworth; Roger Pearce (Planta, 2002)

Stoichiometric food quality and herbivore dynamics - Erik B. Muller; Roger M. Nisbet; Sebastiaan A. L. M. Kooijman; James J. Elser; Edward McCauley (Ecology Letters, 2001)
Herbivores may grow with nutrient or energy limitation, depending on food abundance and the chemical composition of their food. We present a model that describes herbivore growth as a continuous function of two limiting factors. This function uses the synthesizing unit concept, has the hyperbolic Monod model as a limiting case, and has the same number of parameters as the Monod model coupled to Liebig’s discontinuous minimum rule. We use the model to explore nutrient‐limited herbivore growth in a closed system with algae, Daphnia and phosphorus as the limiting nutrient. Phosphorus in algae may substantially influence Daphnia growth. This influence changes over time and is most pronounced when algae and Daphnia populations fluctuate strongly. Relative to classic models that only consider food quantity as a determinant of Daphnia growth, our model shows richer dynamical behaviour. In addition to the standard positive equilibrium, which may be stable or unstable depending on nutrient availability, a new positive equilibrium may arise in our model when mortality rates are relatively high. This equilibrium is unstable and reduces the likelihood of long‐term persistence of Daphnia in the system.

Diversity, genetic structure and evidence of outcrossing in British populations of the rock fern Adiantum capillus‐veneris using microsatellites - K. V. Pryor; J. E. Young; F. J. Rumsey; K. J. Edwards; M. W. Bruford; H. J. Rogers (Molecular Ecology, 2001)
Microsatellites were isolated and a marker system was developed in the fern Adiantum capillus‐veneris . Polymorphic markers were then used to study the genetic diversity and structure of populations within the UK and Ireland where this species grows at the northern edge of its range, requiring a specific rock habitat and limited to a few scattered populations. Three dinucleotide loci detected a high level of diversity (23 alleles and 28 multilocus genotypes) across the UK and Ireland, with nearly all variation partitioned among rather than within populations. Of 17 populations represented by multiple samples, all except four were monomorphic. Heterozygosity was detected in three populations, all within Glamorgan, Wales (UK), showing evidence of outcrossing. We make inferences on the factors determining the observed levels and patterns of genetic variation and the possible evolutionary history of the populations.

pGreen: a versatile and flexible binary Ti vector for Agrobacterium-mediated plant transformation - Roger P. Hellens; E. Anne Edwards; Nicola R. Leyland; Samantha Bean; Philip M. Mullineaux (Plant Molecular Biology, 2000)

Synthesis of a spin-labeled photoaffinity ATP analogue, and its use to specifically photolabel myosin cross-bridges in skeletal muscle fibers - Donald Wang; Yin Luo; Roger Cooke; Jean Grammer; Edward Pate; Ralph G. Yount (Journal of Muscle Research and Cell Motility, 1999)

Finite volume discretization with imposed flux continuity for the general tensor pressure equation - Michael G. Edwards; Clive F. Rogers (Computational Geosciences, 1998)

Large-Eddy Simulation of Windbreak Flow - Edward G. Patton; Roger H. Shaw; Murray J. Judd; Michael R. Raupach (Boundary-Layer Meteorology, 1998)

Turbulent kinetic energy budgets from a large-eddy simulation of airflow above and within a forest canopy - Michael J. Dwyer; Edward G. Patton; Roger H. Shaw (Boundary-Layer Meteorology, 1997)

Bibliography the after-cooking discoloration of potatoes - Eugene A. Talley; Mary V. Zaehringer; Roger M. Reeve; R. B. Hyde; Donald H. Dinkel; Edward G. Heisler; Russell Pressey (American Journal of Potato Research, 1969)